Seed Oil Quality of Brassica napus and Brassica rapa Germplasm from Northwestern Spain - Elena Cartea; Antonio De Haro-Bailón; Guillermo Padilla; Sara Obregón-Cano; Mercedes del Rio-Celestino; Amando Ordás (Foods, 2019)
The seed oil content and the fatty acid composition of a germplasm collection of Brassica napus and Brassica rapa currently grown in Galicia (northwestern Spain) were evaluated in order to identify potentially interesting genotypes and to assess their suitability as oilseed crops for either edible or industrial purposes. The seeds of the B. rapa landraces had higher oil content (mean 47.3%) than those of B. napus (mean 42.8%). The landraces of both species showed a similar fatty acid profile (12% oleic acid, 13% linoleic acid, 8−9% linolenic acid, 8−9% eicosenoic acid, and 50−51% erucic acid). They were very high in erucic acid content, which is nutritionally undesirable in a vegetable oil, and very low in oleic and linoleic acid contents. Therefore, they could be used for industrial purposes but not as edible oil. The erucic acid content ranged from 42% to 54% of the total fatty acid composition with an average value of 50% in the B. napus landraces whereas in B. rapa, it ranged from 43% to 57%, with an average value of 51%. Considering the seed oil and the erucic acid content together, three varieties within the B. napus collection and two varieties within the B. rapa one seem to be the most promising genotypes for industrial purposes.